Study of management and development of Observatorium Astronomi ITERA Lampung (OAIL) area: Part I - A. N. I. Putri; W. Z. Ilmi; A. Vatikawa; N. Pratiwi (Journal of Science and Applicative Technology, 2019)
Institut Teknologi Sumatera (ITERA) and Institut Teknologi Bandung (ITB) also Government of Lampung Province have launched the ITERA Astronomical Observatory or known with Observatorium Astronomi ITERA Lampung (OAIL). On 20th November 2016, the coordinates of the observatory were determined 05o 27â€™ 71â€ S and 105o 09â€™ 39â€ E with height of 1030 above sea level. Development of OAIL area will be the center of education in science field especially in Atmospheric and Planetary Sciences. OAIL also will become the center of ecotourism in Lampung Province which can become a tourist attraction for the people in Lampung even outside Lampung. Therefore, it is necessary that management and development be directed so that the main function of the observatory is not disturbed. In this research will do assessment about OAIL area by distribute questionnaire to some related agencies to evaluate whether OAIL area can be a specific area or not. From 50 respondents, there are 35 respondents say that OAIL area is appropriate as a specific area and 15 respondents say vice verca.